2013
DOI: 10.29173/cais331
|View full text |Cite
|
Sign up to set email alerts
|

Covered Beverages Now Allowed: Public Libraries and Book Superstores

Abstract: Unobtrusive observation was used to investigate what people do while at public libraries and how these behaviours are similar to or different from what commonly happens in book superstores. Public libraries emerge as being more diverse, providing more access to information and reading materials, and functioning as a democratic and tolerant public gathering place.Une observation discrète a été effectuée pour étudier ce que les individus font lorsqu’ils fréquentent les bibliothèques publiques et comment ces comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
1
9
0
1
Order By: Relevance
“…There is, however, a rising volume of research that compares public libraries to "superbookstores" as public places. The work of McKechnie et al [25] is probably the closest to our own work from that genre. That research investigated the different behaviors observed in libraries, when compared to large, chain bookstores.…”
Section: Related Workmentioning
confidence: 64%
See 1 more Smart Citation
“…There is, however, a rising volume of research that compares public libraries to "superbookstores" as public places. The work of McKechnie et al [25] is probably the closest to our own work from that genre. That research investigated the different behaviors observed in libraries, when compared to large, chain bookstores.…”
Section: Related Workmentioning
confidence: 64%
“…Intriguingly, our research revealed little work had been undertaken regarding the queries presented at bookstores. Indeed, a comparison of bookstore and library culture was nearly all we could discover [25]. Given the importance of bookstores to reading, this seems a surprising omission, though they have been used as venues for at least one other study [26].…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study of user behaviour in public libraries (McKechnie et al, 2004), a surprise finding was that library patrons frequently violated library rules by engaging in behaviours which disrupted the use of the library by others. Additionally, staff were often seen to ignore or even encourage this behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…However, in practice, there seems to remain a social barrier to peer interactions and focused encounters (Goffman, 1966) between most (unacquainted) library users. The behavioural norm is to work in isolation from other users (Aabo & Audunson, 2012;McKechnie et al, 2004). Physical infrastructure that accommodates and invites social learning is not sufficient to turn a social learning space into a place where social learning is actually being practiced and experienced.…”
Section: Theoretical Framework: Space Place and Sense Of Placementioning
confidence: 99%